The multiple dimensions of poverty : Posadas in the context of urban Argentina - González, Fernando Antonio Ignacio (2018)
Fil: González, Fernando Antonio Ignacio. National Research Council Scientific and Technical. Institute of Economic Research and Social Societies of the South; Argentina.